Paleorekonstrukce vegetačního vývoje krajiny a vzniku vývoje a kolapsu kupovité palsy v Abisku v oblasti Torneträsk (Švédsko) v holocénu - Jankovská, V. (Vlasta); Kociánová, M. (2010)
Pollen- and Non-pollen palynomorphs from a dome-shaped palsa in Abisko were the basis for palaeoreconstruction of vegetation development in the Torneträsk area (Sweden) and of palsa origin and development. 230 cm thick profile covers the last 8000 years. The palsa originated about 2500 years uncal BP after strong temperature decline. Strong decline of Pinus and simultaneous strong expansion of Betula tortuosa and B. nana was observed. Sudden retreat of Cyperaceae and sudden increase of Ericaceae / Vacciniaceae, Rubus chamaemorus proves the origin of palsa.